Successful Treatment of Critically Severe Empyema With Bronchopleural Fistula via ECMO: A Case Report - Shunxin Xin; Zhongliang He; Weihua Xu; Xueming He; Guoxing Chen; Zhongrui Ye; Xia Hong (Respirology Case Reports)
ABSTRACT Empyema is one of the most dangerous complications in thoracic surgery. It can easily progress to severe empyema with life‐threatening conditions that are extremely challenging to treat. We successfully treated a patient with critically severe empyema via extracorporeal membrane oxygenation (ECMO), and the patient eventually recovered and was discharged. A 64‐year‐old male developed empyema 5 years ago. The thoracic infection led to a breakdown of the left chest wall. During hospitalisation, the patient's condition gradually deteriorated. We promptly initiated ECMO support and performed multiple debridement surgeries, fistula closure, targeted anti‐infection treatment, and nutritional support. Ultimately, the patient's condition improved, as he eventually recovered and was discharged.